Classification and types of flaps in endodontic surgery - Rajkhan, Wael Hisham; Alrasheedi, Naif Mayouf; Alsaper, Hatton Khalid; Aljishi, Reem Abdulwahed; Alahmadi, Reem Badi; Abdulbagi, Rogaya Hassan; Kernshi, Kholoud Shergawi; Almalki, Afnan Hassan; Aloqayli, Sarah Hussain; Alrehaili, Hanan Sulaiman; Aljohani, Ghaida Ghazi (International Journal Of Community Medicine And Public Health, 2021)
The success of endodontic surgeries can be significantly associated with the selected dental flap. Many flaps have been reported among studies in the literature with variable frequencies of advantages and disadvantages and with different indications for each flap. This literature review discusses the most commonly reported types of endodontics flaps along with the reported advantages and disadvantages, in addition to the uses, applications, and most probable indications and contraindications for each designed flap. Among the reported flap designs, clinical success and favorable outcomes were observed with the ones that limited the damage to the root-attached tissues. Moreover, crestal bone loss has been reported to be minimal when using the full mucoperiosteal flap designs. Many previous studies have reported that using triangular and rectangular flap designs has been associated with favorable events regarding crestal bone loss, with the observed complete healing of the resorption damaging events and absent alternations of the heights of the crestal bone that were potentially affected. Further details of each flap design are provided within the full manuscript of this article based on the obtained evidence from previous investigations.